Credit accessibility and rural development in the former Ciskei: an overview of Keiskammahoek - Kimemia, Peter Njau (Rhodes University, Faculty of Humanities, Department of Sociology, 2001)
This study focuses on the issue of credit accessibility for the rural poor. Taking cognisance of the critical role played by innovative micro-lending mechanisms in the sphere of rural development, the study reaffirms the need to enhance access to financial services by rural communities. However, it also reveals the fact that there are numerous impediments to access to credit for the people living in parts of the Keiskammahoek District of the former Ciskei. Key among the impediments has been lack of awareness about the existence and the activities of micro-lending institutions. This has, in a large measure been blamed for many of the rural poor people's failure to approach such institutions for funding. As a result, the affected people's efforts to fully actualize themselves economically have to a certain extent been hampered. Consequently, as its core argument, this study views as crucial the need to tackle all the attendant impediments. It also suggests that as the first step, the government, NGOs as well as formal and informal lending institutions should endeavour to disseminate the requisite information on micro-financing and in enhancing the affected people's institutional capacity to effectively use credit obtained for commercially productive ventures. Without sorting out the basics first, credit extension even when easily availed may not have the desired impact. At worst, it may actually complicate the poverty situation as the people grapple with piling debts.
Keywords: Credit -- Research -- South Africa -- Ciskei; Rural development -- South Africa -- Ciskei; Poor -- South Africa -- Ciskei; Poor -- Developing countries